AN ECOTOURISM MODEL FOR SOUTH AFRICAN NATIONAL PARKS - Leonie de Witt (Tourism & Management Studies, 2011)
South Africa boasts with twenty-one national parks which are under the management of South African National Parks (SANParks). SANParks is the leading conservation organisation in South Africa and also the largest provider of ecotourism experiences in the country. Ecotourism has become one of the world’s major economic sectors with the capability to play a significant role in the sustainable development in areas where nature attracts tourists (Powell & Ham, 2008:467; Fennel, 2002:12). As an ecotourism provider it is important that SANParks implement an ecotourism model to successfully develop and manage its ecotourism products. The absence of such a model can constrain tourism products’ functionality to deliver a competitive product in an extremely competitive industry (Cloete, 2001:2). Although the core pillars on which SANParks management operations are based, are aligned with ecotourism principles, it was found that no concrete model is currently in place to show how ecotourism should be developed and managed in South African National Parks. Hence the aim of this study is to determine what the key aspects for an ecotourism model in South Africa would be.